Do behavioral patterns of university students of Nepal make them vulnerable to HIV/AIDS? - Joshi, DR; Khatri, DB; Rosyara, KP; Malla, B (Journal of Institute of Medicine Nepal, 2008)
Introduction: Nepal is confronted with the increasing incidence of HIV among young adults. The University students at their age are at increased risk of the disease, determined by their behaviors Thus, Assessment of knowledge, attitude, and beliefs of them are essential prior to implementation of prevention and control strategies. Methods: This cross sectional study was carried out in 2006 among university students at Tribhuvan University, Kirtipur, Nepal. A total of 100 students participated from different departments. The questionnaire design included background characteristics, condom use, knowledge and opinion towards HIV/ AIDS, Sexual risk behavior and sexual relation, symptoms on STI and HIV/ AIDS, stigma and discrimination regarding HIV/AIDS. Results: The median age of male respondents was 26 years and that of female was 23 years. Among married respondents (16.7%), female respondents were married at younger age (F=23yrs, M=24yrs). The majority of them were unemployed (78.1%). The major sources of information regarding HIV/ AIDS were television (95.8%) and radio (91.7%). Only 13.5% of respondents (F=12%, M=15.2%) knew about voluntary counseling and testing services (VCT). The age of first sexual intercourse was 22 years; same for both men and women. Among them, 65.4 % admitted using condoms during first intercourse. Family planning centre was the major condom supply source (78.1%). Use of condoms was the most common perceived method of protection against HIV/AIDS for both male (93.5%) and female (78%). Seventy- nine percentage of respondents maintained that HIV is transmitted by sharing of food, and mother to child, and HIV+ individuals looked healthy. Conclusions: This study provides empirical evidence of stirring knowledge about HIV and sexual behavior among adults; however; needs further examination through a longitudinal study. Key words: Sexual behaviour, human immunodeficiency virus The full text of this paper is available at Journal of Institute of Medicine website